Keterbukaan Ekonomi Sektor Perikanan di Provinsi Maluku: Aplikasi Error Correction Model (ECM) - Manuhutu, Yerimias; Yoseph, Fenty; Pauline, Vera (Jurnal Trikonomika, 2011)
Maluku is a province that comprised 92 percent of the ocean so rich in marine resources and fisheries. In this study focuses on the analysis of fishery exports and macro variables in the region. The dependent variable was the fisheries exports (Y), while the independent variable is the target of observation is the investment variable (X1), the inflation variable (X2), the exchange rate variable (X3) and variable of labor (X4). Data used in this study originated from the BPS, BI and the Department of Marine and Fisheries Maluku Province. The method used in this study is EG-ECM (Engle Granger - Error Correction Model). Results showed that in the short term and long-term inflation variable has a significant and negative relation with fisheries export, exchange rate variable have a significant and positive relation with fisheries export. Labor has a significant in the long term while no effect on short-term fisheries export. Investment variable in both the long-term and short term is not significant in influencing the fisheries exports. ECT is a significant value indicates that the model used in this study is valid.